2021
DOI: 10.1515/ami-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variation in the migratory behaviour of a generalist seabird, the herring gull (Larus smithsoniansus), from the Canadian Arctic

Abstract: The Arctic is warming three times faster than the rest of the globe, causing rapid transformational changes in Arctic ecosystems. As these changes increase, understanding seabird movements will be important for predicting how they respond to climate change, and thus how we plan for conservation. Moreover, as most Arctic-breeding seabirds only spend the breeding season in the Arctic, climate change may also affect them through habitat changes in their non-breeding range. We used Global Location Sensors (GLS) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…The remaining individuals moved considerably further (up to 185 km). These migration distances were similar, or slightly shorter, to those estimated for herring gulls in the Netherlands based on ringing recoveries (Camphuysen et al, 2011), and considerably shorter than observed for American herring gulls (Larus smithsoniansus) breeding in northeastern North America (Anderson et al, 2019;Baak et al, 2021), possibly reflecting the mild oceanic climate of coastal Western Europe compared to northeastern North America.…”
Section: Discussionsupporting
confidence: 74%
“…The remaining individuals moved considerably further (up to 185 km). These migration distances were similar, or slightly shorter, to those estimated for herring gulls in the Netherlands based on ringing recoveries (Camphuysen et al, 2011), and considerably shorter than observed for American herring gulls (Larus smithsoniansus) breeding in northeastern North America (Anderson et al, 2019;Baak et al, 2021), possibly reflecting the mild oceanic climate of coastal Western Europe compared to northeastern North America.…”
Section: Discussionsupporting
confidence: 74%
“…The structure of these assemblages demonstrates that, from a conservation perspective, environmental and anthropogenic stressors in the northern Gulf can have effects that extend across much of the north-south and eastwest footprint of the Atlantic basin. As the understanding of the behavior of seabirds occurring in the nGoM increases through tracking (e.g., [62][63][64][65]), the connectivity of the nGoM to other regions will be revealed with increasing detail.…”
Section: Plos Onementioning
confidence: 99%
“…increasing as the number of seasons with an occurrence increase (King and Sanger, 1979). Interannual variation in environmental conditions can impact seabird distributions, altering their exposure to threats (Baak et al, 2021;Bi et al, 2021). Therefore, seasonal occurrence can capture interannual differences in occurrence, whereas describing broad-scale distribution patterns (e.g., residency, described below) is not sensitive to this variation.…”
Section: Seasonal Occurrence Within the Study Areamentioning
confidence: 99%
“…Uncertainty in residency could be reduced by increasing the understanding of seabird movements across their annual cycle, including the degree of individual and interannual variation in movement patterns. Lagrangian methods, such as individualbased tracking, can be used to better understand variation in migration patterns (Baak et al, 2021), habitat use (Jodice et al, 2015;McCloskey et al, 2018;Phillips et al, 2018), and overlap with threats (Lamb et al, 2018;Isaksson et al, 2021). Tracking has identified previously unknown breeding areas (Kanai et al, 2002) and demonstrated links with distant colonies with seabirds using the nGoM (Montevecchi et al, 2012).…”
Section: Uncertaintymentioning
confidence: 99%